Earlywood and Latewood Stable Carbon and Oxygen Isotope Variations in Two Pine Species in Southwestern China during the Recent Decades - Fu, Pei-Li; Grießinger, Jussi; Gebrekirstos, Aster; Fan, Ze-Xin; Bräuning, Achim (Frontiers in Plant Science, 2017)
Stable isotopes in wood cellulose of tree rings provide a high-resolution record of environmental conditions, yet intra-annual analysis of carbon and oxygen isotopes and their associations with physiological responses to seasonal environmental changes are still lacking. We analyzed tree-ring stable carbon (δ13C) and oxygen (δ18O) isotope variations in the earlywood (EW) and latewood (LW) of pines from a secondary forest (Pinus kesiya) and from a natural forest (Pinus armandii) in southwestern China. There was no significant difference between δ13CEW and δ13CLW in P. kesiya, while δ13CEW was significantly higher than δ13CLW in P. armandii. For both P. kesiya and P. armandii, δ13CEW was highly correlated with previous year’s δ13CLW, indicating a strong carbon carry-over effect for both pines. The intrinsic water use efficiency (iWUE) in the earlywood of P. armandii was slightly higher than that of P. kesiya, and iWUE of both pine species showed an increasing trend, but at a considerably higher rate in P. kesiya. Respective δ13CEW and δ13CLW series were not correlated between the two pine species and could be influenced by local environmental factors. δ13CEW of P. kesiya was positively correlated with July to September monthly mean temperature (MMT), whereas δ13CEW of P. armandii was positively correlated with February to May MMT. Respective δ18OEW and δ18OLW in P. kesiya were positively correlated with those in P. armandii, indicating a strong common climatic forcing in δ18O for both pine species. δ18OEW of both pine species was negatively correlated with May relative humidity and δ18OEW in P. armandii was negatively correlated with May precipitation, whereas δ18OLW in both pine species was negatively correlated with precipitation during autumn months, showing a high potential for climate reconstruction. Our results reveal slightly higher iWUE in natural forest pine species than in secondary forest pine species, and separating earlywood and latewood of for δ18O analyses could provide seasonally distinct climate signals in southwestern China.